ANALISIS KOMPETENSI DAN PERMASALAHAN DALAM MENULIS ARTIKEL PADA MATA KULIAH ACADEMIC WRITING - Sri Lestari; Tri Wahyuni Chasanatun (Jurnal Penelitian LPPM (Lembaga Penelitian dan Pengabdian kepada Masyarakat) IKIP PGRI MADIUN, 2016)
This research is aimed to: (1) observe and describe academic writing teaching learning in classroom, (2) analyze students' achievement and development in writing article, (3) analyze students' problems and difficulties in writing article. The research was conducted in IKIP PGRI Madiun. The population was the fourth semester students of English Department IKIP PGRI Madiun in the academic year of 2013/2014. The research method was case study. Technique of collecting data was qualitative data; students' portfolios, observation, and interview. Techniques of analysis of data were: data reduction, data display, data verification. The research findings show that: (1) lecturer has done taught academic writing based on the syllabus and lesson plan; and students joined the class active, tried to write maximal, shared with friends and peers, (2) students' competences in writing article did not improve significantly, there were some students still get low score and still difficult in brainstorming idea and choosing topic, some students also had mistakes in grammar, (3) there were some mistakes that students done in writing article, they were: choosing appropriate grammar, vocabulary, mechanics appropriately, and difficult in quoting references